2020
DOI: 10.1186/s43055-020-00238-7
|View full text |Cite
|
Sign up to set email alerts
|

Presence of vascular loop in patients with audio-vestibular symptoms: is it a significant finding? Evaluation with 3-tesla MRI 3D constructive interference steady state (CISS) sequence

Abstract: Background Tinnitus, sensory neural hearing loss (SNHL), and vertigo are common audio-vestibular symptoms. Many diseases are associated with these symptoms; however, the exact cause is not always identified. Some studies show that the etiology could be related to the presence of a vascular loop in contact with the 8th cranial nerve. Three-dimensional (3D) constructive interference in steady state (CISS) is a fully refocused gradient-echo magnetic resonance imaging (MRI) sequence that has high sensitivity in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Although there have been studies that have found no correlation between the vascular loops and SNHL/tinnitus, there have been reports which have shown MVD of the vascular loop completely or partially resolving symptoms of tinnitus, vertigo, or SNHL [9,[17][18][19][20]. Furthermore, the establishment of a normalized grading scale will allow physicians to understand the pathology and determine whether to start with surgical or medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been studies that have found no correlation between the vascular loops and SNHL/tinnitus, there have been reports which have shown MVD of the vascular loop completely or partially resolving symptoms of tinnitus, vertigo, or SNHL [9,[17][18][19][20]. Furthermore, the establishment of a normalized grading scale will allow physicians to understand the pathology and determine whether to start with surgical or medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we elected to verify the smallest vertical diameter in addition to conventional dimensions in both the axial and coronal planes to avoid misdiagnosis. In fact, the association between otological symptoms and vascular loop are still controversial [ 58 , 59 , 60 , 61 , 62 ]. This relationship has been related to the loop location following Chavda classification [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many diseases can cause these symptoms to occur. However, the exact cause cannot be determined most of the time (6).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in MRI sequences have enabled detailed visualization of vascular structures and cranial nerves (7). MRI provides very useful information in patients with audiovestibular dysfunction (6).…”
Section: Introductionmentioning
confidence: 99%